O avesso das mentiras: entre loucuras e potências, a escrita de nós - Costa, Janaina da Silva (2023)
The research proposes to show the reverse of single stories told about black women in institutional care. With the sustitution of “black women as a research object” to “black women telling their own story”, their narratives are brought from the methodological paths of escrevivência, presented by Conceição Evaristo. Thus, the reasons that put them in the homeless situationl an then to institucional care are narrated together with them. Considering intersectionality as an analysing concept, the text walks with social makers such as gender, race, social class and psychic condition, asserting that crazy women can and should talk about themselves.The representation of the reverse side comes with Elisa Lucinda and O pensamento de Edite, with the image of the reverse side of the embroidery as the inside of the person. And Chimamanda Ngozi Adichie complements, launching the movement of learning to disbelieve the single stories that were told to them; this movemente that the women who make up the research also invite us to, by presenting their reverses. Having black feminist epistemologies as a theoretical framework, the writing charged witl afecction proposes an immmersion in Afro-Brazilian reading, decolonial and against sexcism, presenting localized knowledge arising from the proposal of an Afrodiasporic academy.